Airline ticket reservation using NFC-based single identity - Mikhael Bagus Renardi; Noor Cholis Basjaruddin; Supriyadi Supriyadi; Kuspriyanto Kuspriyanto (Institute of Advanced Engineering and Science, 2019)
Airline ticket reservations can be completed via ticket counters or online. To reduce passenger data redundancy, Single Identity (SI) may be required to input passenger data. In Indonesia, SI is utilised in identity cards using Near Field Communication (NFC), called electronic Kartu Tanda Penduduk (e-KTP). However, the use of e-KTP is not optimal yet because it is still used in the same way as the conventional one. Data input using SI can be done by tapping the e-KTP on a NFC-enabled machine, and the user is required to select the passengers’ names. The process of data input may be simplified, resulting in a higher transaction speed. This research result demonstrated that there was a slight difference of the time required between the two methods for ticket reservations. The time efficiency using SI through ticket counters was 48%, while the online reservation using SI was 45%. Further research may implement the validation methods, such as using PIN or fingerprint.